MODALITY AND NEW ARENA: NU AND MUHAMMADIYAH IN THE LOCAL ELECTION GUNUNG KIDUL REGENCY - Harirah MS, Zulfa (Department of Government, FISIP, Universitas Padjadjaran, 2021)
The relation of NU - Muhammadiyah in the history of modern Indonesia is indeed very interesting. Throughout the course of this largest Islamic organization is often colored by coordination, competition, and even confrontation. Reflecting on the Regent's election contestation in Gunung Kidul Regency, Yogyakarta became a real